1996
DOI: 10.1152/jn.1996.75.2.894
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic GABAB receptors modulate IPSPs evoked in neurons of deep cerebellar nuclei in vitro

Abstract: 1. Recording from deep cerebellar nuclei neurons, we investigated the role of presynaptic gamma-aminobutyric acid-B (GABAB) receptors in the modulation of monosynaptic inhibitory postsynaptic potentials (IPSPs) evoked by stimulation of Purkinje cells in rat slice cultures. 2. Bath application of the GABAB receptor agonist, baclofen (10 and 100 microM) induced two effects in cerebellar nuclei neurons: a postsynaptic hyperpolarization of 4.2 +/- 1.7 (SD) mV and a reduction in the amplitude of evoked IPSPs (30 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
3
12
1
1
Order By: Relevance
“…Furthermore, our results indicate that these properties differ from those of the synapses made between PCs and their target neurons at the DCN. We find that PC-PC synapses facilitate for short interpulse intervals, whereas the paired-pulse ratio for PC-DCN synapses is close to 1 in organotypic cultures (23,24), and the synapse is strongly depressing in acute slices from rats (25) and mice (26,27). Concerning train behavior, PC-DCN synapses show moderate (23) or substantial (26,27) depression during trains, which contrasts with the summating response to trains found in the present work (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, our results indicate that these properties differ from those of the synapses made between PCs and their target neurons at the DCN. We find that PC-PC synapses facilitate for short interpulse intervals, whereas the paired-pulse ratio for PC-DCN synapses is close to 1 in organotypic cultures (23,24), and the synapse is strongly depressing in acute slices from rats (25) and mice (26,27). Concerning train behavior, PC-DCN synapses show moderate (23) or substantial (26,27) depression during trains, which contrasts with the summating response to trains found in the present work (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…GABA binds to and mediates its effects via post-synaptic ionotropic GABA A receptors and pre-and post-synaptic metabotropic GABA B receptors 19,20. Whereas the GABA A receptors mediate fast responses, the GABA B receptors mediate slow responses.…”
Section: Introductionmentioning
confidence: 99%
“…A neuropathological study in 199620 revealed that GABA B receptors are present on the presynaptic terminals of Purkinje cells in the deep cerebellar nuclei. These anatomical structures have since been considered involved in the probable genesis of ET.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations